Degradation of toxic PAHs in water and soil using potassium zinc hexacyanoferrate nanocubes. (15th December 2017) - Shanker, Uma; Jassal, Vidhisha; Rani, Manviri
Abstract: Polycyclic aromatic hydrocarbons (PAHs) the ubiquitous, persistent and carcinogenic environmental contaminants have raised concern worldwide. Recently, their removal methodologies are advanced after exploring nanomaterials. Therefore, degradation of selected toxic PAHs (3–5 rings) using potassium zinc hexacyanoferrate (KZnHCF) nanocubes was studied. Highly crystalline and sharp KZnHCF nanocubes (∼100 nm) were obtained by green route using sapindus mukorossi . In both water and soil, anthracene and phenanthrene were degraded to maximum extent (80–93%), whereas, the degradation of fluorene, chrysene and benzo ( a ) pyrene were ∼70–80%.Because of small size (lower molecular weight), large number of anthracene and phenanthrene molecules were adsorbed on catalyst as compared to other PAHs. Higher degradation of PAHs in water than in the soil is attributed to the easy absorption of PAHs on catalyst in water and slow diffusion of PAHs on organic content of soil. PAHs were degraded at the concentration of 50 mg/L, 25 mg catalyst dose, neutral pH and solar irradiation. Higher proficiency of the catalyst was revealed by degradation of PAHs into small and non-toxic by-products such as malealdehyde, 4-oxobut-2-enoic acid and o -xylene. Overall, the potential KZnHCF nanostructures open future scope for eradication of other pollutants from the environment. Graphical abstract: Highlights: A comprehensive study on photodegradation of PAHs (3–5 rings) in water and soil. KZnHCF nanocubes as potential adsorbent cum photocatalyst: sunlight > UV light > dark. Adsorption was found dependent of size and molecular weight of PAHs. Higher degradation of PAHs in water than in the soil is attributed to high efficiency of KZnHCF.